2018
DOI: 10.2139/ssrn.3244898
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Early Life Mental Health and Alcohol Use Behaviours in Adulthood: A Systematic Review

Abstract: This systematic review aims to summarise current evidence on the association between early life mental health and alcohol use behaviours in adulthood. Peer-reviewed publications were located by searching EMBASE, Medline, PsycINFO, and the ISI Web of Science up to 31 October 2018. Prospective longitudinal studies reporting associations between externalising problems (EXT), internalising problems (INT), depression, anxiety before age 18, and alcohol use behaviours (alcohol consumption, heavy/problematic drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(240 reference statements)
1
1
0
Order By: Relevance
“…It is di cult to determine the chronological sequence of "risky drinking" and other mental health problems because of the cross-sectional design of this study. This result is in accordance with a meta-analysis, which showed that externalizing problems in some studies and depression tended to be positively associated with alcohol use, but there was no clear association between alcohol problems and anxiety 43 . A potential explanation is that people who have a tendency toward behavioral disinhibition are more likely to be involved in restricted actions, especially those who have experienced adverse and highrisk living environments [44][45][46] .…”
Section: Discussionsupporting
confidence: 90%
“…It is di cult to determine the chronological sequence of "risky drinking" and other mental health problems because of the cross-sectional design of this study. This result is in accordance with a meta-analysis, which showed that externalizing problems in some studies and depression tended to be positively associated with alcohol use, but there was no clear association between alcohol problems and anxiety 43 . A potential explanation is that people who have a tendency toward behavioral disinhibition are more likely to be involved in restricted actions, especially those who have experienced adverse and highrisk living environments [44][45][46] .…”
Section: Discussionsupporting
confidence: 90%
“…Mental health problems are a leading cause of health-related disability in children and adolescents [41]. Worldwide, approximately 10-20% of children and adolescents experience mental health problems [42], and mental health problems in childhood or adolescence can also have an impact in adulthood, such as mood disorders or employment difficulties [43]. Schools were closed during the pandemic, and most family activities and group extracurricular activities were canceled.…”
Section: Plos Onementioning
confidence: 99%